Funds Flow in Academic Neurology Departments - Goldstein, Larry B.; Josephson, S. Andrew (Seminars in Neurology, 2025)
The term “funds flow” refers to the financial relationships between the schools or colleges of medicine and its parent university, the hospital/health system, and clinical departments. Funds flow arrangements vary greatly among organizations based on the relationships between these entities, their financial status, levels of extramural research support, and size of endowments and philanthropic activities. We review four general funds flow models: the “Make Whole” Model, the “Pay for Production” Model, the “Value-Based” Model, and the “Contribution Margin” Model. We also discuss issues that can affect how these models operate and the reasons they differ depending on organizational structures and financial postures.
Keywords: all education; medical care; medical education; medical economics